Evolution and Expression of Reproductive Transition Regulatory Genes FT/TFL1 With Emphasis in Selected Neotropical Orchids - Ospina-Zapata, Diego A.; Madrigal, Yesenia; Alzate, Juan F.; Pabón-Mora, Natalia (Frontiers in Plant Science, 2020)
Flowering is a rigorously timed and morphologically complex shift in plant development. This change depends on endogenous as well as environmental factors. FLOWERING LOCUS T (FT) integrates several cues from different pathways acting as a flowering promoter. Contrary to the role of FT, its paralog TERMINAL FLOWER 1 (TFL1) delays floral transition. Although FT/TFL1 homologs have been studied in model eudicots and monocots, scarce studies are available in non-model monocots like the Orchidaceae. Orchids are very diverse and their floral complexity is translated into a unique aesthetic display, which appeals the ornamental plant market. Nonetheless, orchid trade faces huge limitations due to their long vegetative phase and intractable indoor flowering seasons. Little is known about the genetic basis that control reproductive transition in orchids and, consequently, manipulating their flowering time remains a challenge. In order to contribute to the understanding of the genetic bases that control flowering in orchids we present here the first broad-scale analysis of FT/TFL1-like genes in monocots with an expanded sampling in Orchidaceae. We also compare expression patterns in three selected species and propose hypotheses on the putative role of these genes in their reproductive transition. Our findings show that FT-like genes are by far more diversified than TFL1-like genes in monocots with six subclades in the former and only one in the latter. Within MonFT1, the comparative protein sequences of MonFT1A and MonFT1B suggest that they could have recruited functional roles in delaying flowering, a role typically assigned to TFL1-like proteins. On the other hand, MonFT2 proteins have retained their canonical motifs and roles in promoting flowering transition. This is also shown by their increased expression levels from the shoot apical meristem (SAM) and leaves to inflorescence meristems (IM) and floral buds (FBs). Finally, TFL1-like genes are retained as single copy and often times are lost. Their loss could be linked to the parallel recruitment of MonFT1A and MonFT1B homologs in delaying flowering and maintaining indeterminacy of the inflorescence meristem. These hypotheses lay the foundation for future functional validation in emerging model orchid species and comparative analyses in orchids with high horticultural potential in the market.